Inhibition of the Bacillus subtilis Membrane-Bound d-Alanine Carboxypeptidase by 6-Aminopenicillanic Acid Covalently Coupled to Sepharose - Storm, Daniel R. (1974)
An insoluble penicillin derivative, 6-aminopenicillanic acid covalently coupled to Sepharose, was used to investigate the location of the d-alanine carboxypeptidase in the Bacillus subtilis membrane. Only 50% of the enzymatic activity in protoplasts and 74% of that in purified membranes was sensitive, although the purified enzyme could be inhibited completely by the resin. These results suggest that a minimum of 50% of the d-alanine carboxypeptidase exists on the outer face of the bacterial membrane.